Construire le monde du hardcore - Mueller, Alain (Seismo, 2019)
An invitation to an ethnographic journey in the world of hardcore punk and beyond, this study explores the plurality of practices underlying the existence of this "music-based subculture." Based on a fine-grained, in-depth multi-sited and mobile ethnographic study of more than ten years, this journey brings the reader to the most local galleries of this underground scene. From the umpteenth basement of a Yokohama club to a shack in the middle of the University of San Diego, via Gothenburg, Tokyo, Geneva or Lyon, a whole repertoire of aesthetic, ideological, discursive and bodily logics and conventions is uncovered and analyzed. Hardcore punk, a radical reinterpretation of punk, both from a musical and an ideological point of view, first appeared on the East Coast of the United States in the early 1980s. Although it has since spread on a (quasi-)global scale, it remains unknown to the general public and has attracted little interest from the social sciences or the press, with rare exceptions focusing on its most spectacular aspects: exacerbated aggression, electric music, ideological positions in strong opposition to the "dominant system." This monograph intends to go beyond these caricatural representations and adopts an anthropological perspective on the daily lives of so-called hardcore-kids, but also on all the collective mediations deployed to build the world of hardcore punk.